An Influence Analysis Of Website Service Quality Based On Webqual Version 4.0 Toward Customer Satisfaction - Dewi Insyirahti Salsabilla; Embun Duriany Soemarso; Suko Raharjo (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research aims to analyze the significance of the effect of Usability (US), Information Quality (IQ), Service Interaction Quality (SIQ) on Customer Satisfaction (CS) of PT BTN (Persero) Sharia Semarang Branch Office, both simultaneously and partially. The population in this study is all customers of PT BTN (Persero) Sharia Semarang Branch Office who used website, while the samples in this study were 75 customers of PT BTN (Persero) Sharia Semarang Branch Office who were selected using accidental sampling (haphazard sampling) sampling and purposive sampling (judgment sampling). The data used in this study are primary data collected using a questionnaire. The analysis model used in this study is a multiple linear regression analysis model, while the analysis technique uses the simultaneous significance test (F-test), the coefficient of determination test (R2), and the partial significance test (t-test) which is processed with the SPSS 25.00 program. The results of the hypothesis verification and discussion indicate that Usability (US), Information Quality (IQ), and Service Interaction Quality (SIQ) simultaneously have a significant effect on Customer Satisfaction (CS). Furthermore Information Quality (IQ) and Service Interaction Quality (SIQ) partially related positively and significantly to Customer Satisfaction (CS) while Usability (US) partially proved positive and not significantly to Customer Satisfaction (CS) of PT BTN (Persero) Sharia Semarang Branch Office.